Identification of ornamental plant species in the Martelu Purba Nature Reserve, North Sumatra. Issue 1 (1st December 2022) - Rambey, R; Permana, J
Abstract: Indonesia has a fairly high biodiversity, both flora and fauna. One of the biodiversity in Indonesia is various species of ornamental plants found in the wild. One of the locations that has a diversity of ornamental plant species is the Martelu Purba Nature Reserve. The purpose of this study was to identify the species of ornamental plants found in the Martelu Purba Nature Reserve. The method used in this research is the roaming method, namely by exploring the Martelu Purba nature reserve and then noting the species of plants that have the potential to be ornamental. The results obtained indicate that there are 19 species of ornamental plants at that location. The species of ornamental plants include the family Araceae, Orchidaceae and species of ferns. There are plants that live Epiphyte and several other species grow terrestrially.